Co-assembled supramolecular hydrogels of doxorubicin and indomethacin-derived peptide conjugates for synergistic inhibition of cancer cell growth. Issue 30 (27th March 2019) - Mei, Leixia; He, Suyun; Liu, Ziqi; Xu, Keming; Zhong, Wenying
Abstract : Co-assembly of doxorubicin and a NSAID-based self-assembling peptide conjugate promotes synergistic inhibition of cancer cell growth. Abstract : Conjugation of indomethacin with a self-assembling peptide moiety affords co-assembled supramolecular nanostructures of doxorubicin and peptide derivatives for tunable release of two drugs and synergistic effects against cancer cells, which illustrates a simple and effective approach to utilize co-assembled nanostructures for co-delivery of self-complementary drug pairs.